THE EFFECTIVENESS OF THE USE OF COOPERATIVE LEARNING MODEL COURSE REVIEW HOREY TYPE TO THE MATHEMATICS LEARNING OUTCOMES OF GRADE VIII - Linda Tika Aprilia; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The low student learning outcomes are caused by several factors, one of which the learning model used in the less varied and is still centered on the teacher. This study aims to determine the effectiveness of using a cooperative learning model course review horey type to the mathematics learning result of grade VIII. The population in this study were all students of class VIII SMP Negeri 1 Pundong regency Academic Year 2016/2017, which consists of 8 classes. The sampling technique using a random sampling technique to the class and selected class VIII C as an experimental class and class VIII F as a control class. The data was collected using the test method. Tests using Instrument validity, reliability, and distinguishing power. Data analysis techniques used for prerequisite analysis tests include a normality test and a homogeneity test. The hypothesis to test in this study used a two-party t-test and a one-party t-test with a significant level of 5%. Based on mathematics learning result obtained that 1)  and  which means . This means that there is a difference in learning outcomes between the learning of mathematics using cooperative learning model type course review horey with mathematics learning using a direct learning model on the students of VII SMP Negeri 1 Pundong in even semester regency Academic Year 2016/2017. 2)  and  which means . This shows that the learning of mathematics with cooperative learning model type course review horey is more effective than the mathematics learning using direct learning model towards mathematics learning outcomes in VIII grade students of SMP Negeri 1 Pundong in even semester regency academic year 2016/2017.